The Historian and the Source: Some Contemporary Problems in Holocaust Historiography - Nerijus Šepetys (Lietuvos Istorijos Studijos)
When researching and writing the history of the Holocaust, it is crucial not only to select (and match the topic and approach) the main primary sources, but also to find an adequate critical relationship with them. In the case of the historiography of the beginning of the Holocaust (which is also the beginning of the Holocaust in Lithuania), at least in the twenty-first century, such a relationship is often a challenge for the researcher: there is a tendency to automatically rely on, or to question, particular groups of sources (according to origin). This also leads to serious problems in understanding history, some of which the paper attempts to address. For example, how is the possibility of such an understanding disrupted when reliance is placed on specific (accidental) primary sources without questioning the setting and meaning of their origins and ignoring others? Or what is the picture of history that emerges when the attempts to apply both the attitudes of primordial trust and primitive questioning to subjective sources are uncontrolled? Finally, what are the implications of ignoring primary sources for the historical understanding of Holocaust situations, first of all the “pinning down” of testimonies, and then the subsequent processing (writing them down, reworking them, making them up, swiping them)? Importantly, these are questions not only of today’s historical scholarship, but of the Jewish scholars who survived the Catastrophe immediately after the war.